(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
Societal multilingualism refers to the coexistence of multiple languages within a given community or nation. This phenomenon arises due to historical, political, social, and economic factors. This paper explores the dynamics of multilingual societies, the challenges they face, and the benefits they offer. Through an analysis of case studies and linguistic policies, the study highlights how multilingualism can be both a source of social cohesion and conflict. Findings suggest that effective language planning and policies can foster inclusivity and cultural enrichment while mitigating potential disadvantages.